1972
DOI: 10.1002/macp.1972.021530119
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on branching of polyvinylchloride

Abstract: An investigation was carried out on branching of polymers obtained by lauroyl-peroxide or by radiation-initiated polymerization of vinylchloride. As a result, branching shows no dependence on conversion and could be ascribed, a t least partially, to the presence of CHzC1-side groups.A reaction mechanism for this type of branching was proposed. ZUSAMMENFASSUNG:Es wurde die Verzweigung van durch Lauroylperoxid oder Bestrahlung initiiertem Polyvinylchlorid untersucht. Dabei zeigte sich, dal3 der Umsatz keinen Ein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1974
1974
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…42 The methyl branches may form if the same radical propagates after just one Cl shift. 43 Although the probability of head-to-head addition might be expected to remain relatively constant throughout the polymerization process, the probability that the radical undergoes subsequent Cl shifts might have been expected to increase as the propagation rate declines under conditions of monomer starvation. Although this provides a possible explanation for the increases in methyl and ethyl branches, other observations suggest that, for the production of methyl branches, an additional mechanism may also be at work.…”
Section: Scheme 2 Formation Of Defect Structures After Head To Head mentioning
confidence: 99%
“…42 The methyl branches may form if the same radical propagates after just one Cl shift. 43 Although the probability of head-to-head addition might be expected to remain relatively constant throughout the polymerization process, the probability that the radical undergoes subsequent Cl shifts might have been expected to increase as the propagation rate declines under conditions of monomer starvation. Although this provides a possible explanation for the increases in methyl and ethyl branches, other observations suggest that, for the production of methyl branches, an additional mechanism may also be at work.…”
Section: Scheme 2 Formation Of Defect Structures After Head To Head mentioning
confidence: 99%
“…[8] Further propagation from this radical center leads to the formation of a chloromethyl branch (MB, also called branch of type C 1 ). These ÀCH 2 Cl branches are the most frequent short chain branches in PVC (approximately 4/1000 VC units), as is shown by 1 H and 13 C NMR measurements. [8][9][10][11] It is accepted that this well-known type of defect structure is mainly introduced in the chain by the mechanism described above.…”
Section: Introductionmentioning
confidence: 79%
“…[9] The saturated and unsaturated end groups shown in Scheme 1 are the most abundant end groups in PVC. [2,8] The head-to-head addition followed by 1,2-chlorine migration was originally proposed by Rigo et al for the formation of short chain branches in PVC, and later on confirmed by Starnes et al [12,13] There is a consensus in the literature that the Cl-shift reaction proceeds rapidly, so most of the HH linkages formed in the chain by head-to-head additions will immediately disappear and lead to the formation of defect structures as described above. [8,12] Starnes even claims that the head-to-head radical does not add to monomer but always rearranges by a 1,2-chlorine shift of the b-chloro substituent.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…3,4,9,23,[25][26][27][29][30][31][32][33]42,43 The main goal of these investigations was to determine how and to what extent structural defects in PVC are formed.…”
Section: Structural Defects Contentmentioning
confidence: 99%